Inclusivity Footprint Calculator - Ylikoski, Oona; Huttunen, Janette; Korventausta, Miikka; Leino, Mikko; Setälä, Maija (My University, 2026)
This technical report presents the contents and technical description of the Inclusivity Footprint Calculator, a tool developed within the SINCRONY project as part of Task 3.4 Overall integration of recommendations for best inclusive practices in an intersectional lens. The calculator is a web application designed to benchmark inclusivity in various participatory and deliberative practices that engage young people. It comprises a total of 34 questions, structured into five sections derived from SINCRONY D3.3 Integration of Critical Assessment of Practices. These sections are: Inclusion, Youth Voice and Power, Critical Awareness, Recognition, and Impact. Users can choose to benchmark specific sections or all five of them. After answering all questions in the selected sections, users receive an overall inclusivity score, based on their answers, and individual inclusivity scores for each section they have benchmarked. Users also receive recommendations based on existing good practices at different levels of governance, society, and communities. Within the SINCRONY project, the calculator will be used in WP5 Piloting enhancement and innovation pathways. It will also be openly available for public use.